2020
DOI: 10.1097/md.0000000000022133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bedside assistant on outcomes of robotic thyroid surgery

Abstract: The importance of bedside assistants has been well established in various robotic procedures. However, the effect of assistants on the surgical outcomes of thyroid surgery remains unclear. We investigated the effects of a dedicated robot assistant (DRA) in robotic thyroidectomy. We also evaluated the learning curve of the DRA. Between January 2016 and December 2019, 191 patients underwent robotic total thyroidectomy, all of which were performed by a single surgeon. The DRA participated in 93 cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In contrast, three other studies in prostatectomy and nephrectomy involving a combined 636 patients showed no effect on patient outcomes or case length based on the experience of the assistant [ 18 , 20 , 21 ]. Studies of the impact of assistants in 191 robotic-assisted thyroid operations and 105 robotic-assisted Nissen fundoplications came to conflicting results [ 22 , 23 ]. Our work adds to this literature with a much larger sample size of real-world, diverse cases in multiple specialties with various types of assistants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, three other studies in prostatectomy and nephrectomy involving a combined 636 patients showed no effect on patient outcomes or case length based on the experience of the assistant [ 18 , 20 , 21 ]. Studies of the impact of assistants in 191 robotic-assisted thyroid operations and 105 robotic-assisted Nissen fundoplications came to conflicting results [ 22 , 23 ]. Our work adds to this literature with a much larger sample size of real-world, diverse cases in multiple specialties with various types of assistants.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of operative assistant experience on outcomes has been widely studied in many settings, with different results by procedure, institution, and publication [3,[12][13][14][15][16][17][18][19][20][21][22][23]. Most of the existing literature on the effect of the assistant in robotic surgery is limited to robotic-assisted prostatectomy and nephrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperatively, the BA is physically located next to the patient, standing or sitting next to the operating table, while the operating surgeon stands or sits at the separate robot console. The BA’s autonomous performance is therefore critical, according to extensive literature (Collins et al 2021, Kwon 2020, Potretzke et al 2016), not only ensuring the initiation, continuance and successful completion of the procedure but also due to the primary responsibility for the safety of the patient, as argued by Kumar et al (2015). The importance of the role seems closely related to the tasks and activities undertaken, as well as to communication in RAS.…”
Section: Discussionmentioning
confidence: 99%